The textual architecture of the carnival of Daniel Ospina (2018)
This reflection paper, derived from a thesis on the teaching of the understanding of ironic argumentative texts, addresses, in the light of socio discursive interactionism, the possible carnavalized textual architecture that comes from a corpus of 117 opinion columns by Daniel Samper Ospina published between 2014 and 2016 in Semana Magazine (Colombia). From a hermeneutic interest and supported by pragmalinguistic perspectives of the study of verbal irony, traits of the “bajtianian carnival” are identified in the three levels of textual infrastructure (thanks to the traditional argumentative dispositio and the variety of genres), textualization (through investments in Levinson's neogritian principles, according to the Grupo de la Ironía, Alicante, Lengua Española, Griale ) and the enunciative responsibility (as a result of the insertion of absurd enunciators that mask the speaker ́s function ). This reinforces the conception of irony as a carnivalizing textual device of the action of saying, its modes, its voices and its structures